ABU LAIS SAMARKANDI IS A MATURE SCHOLAR FROM MOVAROUNNAHR (Conferencea, 2022)
Nasr ibn Muhammad ibn Ahmad ibn Ibrahim Samarkandi, known by the names "Imam al-Huda", "al-Faqih", and the nickname "Abu Lais", was born in Samarkand in 298/911. During his life, the scientist wrote many works on tafsir (translation and explanation of meanings of the Holy Qur’an), fiqh (Islamic law), usul (the foundations of religion), aqeedah (Islamic faith), and mysticism. There are different opinions about the year of scholar's death in the sources that have come down to us.